2022
DOI: 10.3389/fgene.2022.947126
|View full text |Cite
|
Sign up to set email alerts
|

Targeted re-sequencing on 1p22 among non-syndromic orofacial clefts from Han Chinese population

Abstract: Rs560426 at 1p22 was proved to be associated with NSCL/P (non-syndromic cleft lip with or without the palate) in several populations, including Han Chinese population. Here, we conducted a deep sequencing around rs560426 to locate more susceptibility variants in this region. In total, 2,293 NSCL/P cases and 3,235 normal controls were recruited. After sequencing, association analysis was performed. Western blot, RT-qPCR, HE, immunofluorescence staining, and RNA sequencing were conducted for functional analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…IRF6 is a gene that had been associated with nonsyndromic CL/P, and extensive investigation found that ARHGAP29 expression was decreased in IRF6 knockout mouse, indicating that it may act downstream of IRF6 in craniofacial development, further confirming it has an association with cleft lip and palate. Interestingly, recent study has shown that a rare variant of ARHGAP29 R551T was also identified to be associated with nonsyndromic CLP in Han Chinese population (Li et al, 2022).…”
Section: Arhgap29mentioning
confidence: 99%
“…IRF6 is a gene that had been associated with nonsyndromic CL/P, and extensive investigation found that ARHGAP29 expression was decreased in IRF6 knockout mouse, indicating that it may act downstream of IRF6 in craniofacial development, further confirming it has an association with cleft lip and palate. Interestingly, recent study has shown that a rare variant of ARHGAP29 R551T was also identified to be associated with nonsyndromic CLP in Han Chinese population (Li et al, 2022).…”
Section: Arhgap29mentioning
confidence: 99%